Ossifying fibromyxoid tumour in a child - Che Ahmad, Aminudin; Ibrahim, Sharaf; AH, Hamzaini; Abdullah, Salmi; Mohd Ali, Siti Aishah (Malaysian Medical Associations, 2004)
Ossifying fibromyxoid tumor (OFMT) is a rare benign tumor, most of which occurs in adults with localization in the subcutaneous tissue or muscle of the extremities. A five-year-old girl presented with a mass in her right upper thigh. Due to the large size of the mass (10 x 7 cm), our provisional diagnosis was a soft tissue sarcoma. A tru-cut biopsy showed that the lesion was benign. The mass was excised and has not recurred since. To the best of our knowledge, this patient is the youngest case of OFMT reported in the English literature